A numerical sieve for the Diophantine Equation x4 + 1 = Dy2 - Cohn J.H.E. (Utilitas Mathematica, 2002)
Although an effective method has recently been obtained which completely Solves the equation of the title in positive integers x and y for given D, the method often involves the factorisation of huge integers, which cannot be carried out in practice. The current work attempts to avoid these difficulties, and solves the equation for D < 108.